A Two-Level Factorial Design for Screening Factors that Influence the Decolorization of Congo Red by Serratia marcescens strain Neni-1 (Journal of Environmental Microbiology and Toxicology, 2023)
The toxicity and persistence of Congo Red pollution make it a major threat to both the environment and human health. Biodegradation, which involves the breakdown of pollutants by microbes like bacteria, fungi, and algae, is an attractive and long-term solution to the problem of Congo Red pollution. Optimization techniques such as Response Surface Methodology can further improve biodegradation processes' efficiency, but initial screening is often needed. Using a two-level factorial design, this study successfully screened five parameters (temperature, pH, incubation time, concentration of Congo Red, and sucrose) that affect Congo red's decolorization by Serratia marcescens strain Neni-1. Additionally, it identified three significant parameters that contribute to optimized decolorization of Congo Red: pH, incubation time, and the concentration of Congo Red. Various diagnostic plots were used to analyze the important contributing factors or parameters, including ANOVA, Pareto's chart, and perturbations plot. The two-level factorial conclusion was supported by diagnostic plots such as half-normal, residual vs runs, Cook's distance, Box-Cox, leverage vs runs, DFBETAS, and DFFITS. Consistent with trends in the published literature, this study found that the majority of Congo Red-degrading microorganisms thrive in nearly neutral environments. In future works, RSM can be used to further optimize the parameters that contributed to the decolorization of this bacterium on Congo Red.
Keywords: Two-Level Factorial Design; Screening Factors; Decolorization; Congo Red; Serratia marcescens